Patellar Size Variation at the Quadriceps Tendon–Bone Block Harvest Site: A Magnetic Resonance Imaging Study to Evaluate the Safe Zone for Harvesting a Sufficient Bone Block. Issue 14 (December 2021) - Negrin, Lukas L.; Zeitler, Cornelia; Hofbauer, Marcus
Background: Quadriceps tendon (QT) autografts with and without a bone block are the least studied and least used options for anterior cruciate ligament reconstruction surgery. In particular, there is a lack of literature describing patellar anatomy. Until now, guidelines for patellar bone block harvesting have been based solely on personal experience. In this study, we intended to derive recommendations from physical regularities and objective criteria. Purpose: To determine the maximal, individual-related length and depth of the bone block that can be safely harvested and to provide guidelines to help surgeons make decisions on graft choice. Study Design: Descriptive laboratory study. Methods: The study group consisted of 50 male participants and 50 female participants (mean age, 29.4 ± 7.9 years) who underwent 3.0-T magnetic resonance imaging of their knee. Patellar height was determined at the center of the middle third of the QT insertion on the patella and the medial and lateral endpoints; the depth was measured at the midpoints of the respective heights. Results: The mean width of the QT and the mean thickness were 49.0 ± 7.6 and 7.3 ± 1.0 mm, respectively. The mean patellar thickness in reference to the medial endpoint, the center, and the lateral endpoint was 18.3 ± 2.4, 17.9 ± 2.3, and 15.1 ± 2.3 mm, respectively, whereas the mean patellar height was 35.1 ± 4.1, 36.7 ± 4.2, and 35.1 ± 3.9 mm. In general, the tendon and patellar dimensions were significantly larger in male participants than in female participants ( P = .016). Conclusion: Bone block harvesting, with its depth not exceeding 50% of the patellar thickness and its length accounting for <50% of the patellar height, poses the least risk for a patellar fracture when located medial to midline. If the bone block is excised from the medial half of the central area (the latter is defined by the middle third of the QT insertion), with the outer edge of the saw positioned at the medial border of the central area, a graft of 15 mm length, 10 mm width, and 8 mm depth can be safely harvested in all White male participants and almost all female participants taller than 165 cm, according to our findings. Clinical Relevance: This is the first study presenting recommendations for patellar bone block harvesting at the quadriceps tendon insertionbased on physical regularities and objective criteria and not on personal experience.